EFFECTIVENESS OF PRACTICE IN GYMNASTICS AND THE PROCESS OF PHYSICAL EDUCATION OF STUDENTS - Karimov, D.D. (SCIENCE and SOCIETY, 2025)
The article studies the effectiveness of gymnastics practice within the framework of school physical education, analyzing historical perspectives, pedagogical strategies, and modern research results. Through a comprehensive literature review and discussion of current methodologies, the article identifies important conditions for improving the physical education results of gymnastics classes.